The Effect of Shariah Governance Implementation on Financial Performance via Corporate Social Responsibility - Fernanda, Hadiana; muslichah, muslichah (STIE Malangkucecwara, 2025)
Islamic banks demonstrate economic stability through the implementation of shariah-based business models and operational principles, particularly in reporting, especially in shariah governance implementation and corporate social responsibility (CSR) reporting. This study investigates how disclosures by the board of directors (BOD), shariah supervisory board(SSB), and audit committee(AC) impact financial performance, with CSR acting as a mediating variable. The research sample comprises Islamic banks in Indonesia from 2019 to 2023, the research sample consist of 12 Islamic banks in Indonesia, resulting in a total of 60 observations. Findings indicate that the BOD positively influences financial performance, while the supervisory board and audit committee exert an adverse effect. Additionally, CSR acts as a mediating variable between shariah governance implementation and financial performance. Institutions that acknowledge this importance are more inclined to dedicate adequate resources and focus to the development of effective CSR programs.